Non-ferrous metal artefacts from the northern Lowveld, South Africa, ca. 1000 CE to ca. 1880 CE. (April 2019) - Miller, Duncan; Killick, David
Abstract: We report metallographic studies of copper ingots and metal artefacts recovered during sporadic surface surveys and excavations over the past fifty years in the northern Lowveld of South Africa. These include primary copper ingots, copper droplets or prills, a nodule of tin bronze, a bimetallic copper/iron ingot, cast copper bars and rods, and finished items like finger rings and beads. Metallographic study of these items shows that copper smelters had difficulty in controlling reducing conditions sufficiently to prevent the co-reduction of iron, despite the use of smaller furnaces for copper smelting than local iron production. Copper probably was refined by melting in crucibles, allowing the iron contaminant to float to the surface, where it was skimmed off. Despite former suggestions to the contrary by geologists, brass could not have been produced locally by smelting of zinc‑copper ores from the Murchison Range. Bronze and brass first appeared in this region at the end of the thirteenth century CE, probably as imports from the Islamic world. Highlights: Archaeological research around Phalaborwa has produced diverse copper-alloy artefacts. Metallic iron inclusions in copper reveal the co-reduction of iron. Subsequent refinement of copper may have been a routine processing step. A unique bimetallic ingot of copper and high phosphorus cast iron was discarded. Smelting of zinc‑copper ores could not have produced brass locally.